Modern power system reliability assessment with cyber-intrusion on heat pump systems - Gündüz, Hasan; Jayaweera, Dilan (Inst Engineering Technology-Iet, 2020)
In smart power systems, information and communication technologies are being broadly installed and two-way communications are being established more effectively and efficiently. However, they are vulnerable to cyber-physical interactive threats and their impact depends on the system infrastructure, degree of interaction, degree of vulnerability, and the intensity and the frequency of the attack. The study addresses this problem and proposes: (i) an innovative Markov-chain based framework of the cyber-intrusion process to implement operating conditions in a smart power system; (ii) an advanced algorithm for power system reliability assessment, incorporating cyber-intrusion process and a detailed model of a heat pump system; and (iii) a new impact assessment framework for different cyber-intrusion detection-time distributions driven by Monte Carlo simulation. The cyber-detection and system recovery process with the presence of cyber-physical interactive operation models suggest that a significant level of impacts could be generated by the interactive operation of the smart power system and a quantitative assessment is needed in order to assess true impacts.
GUNDUZ, HASAN/0000-0003-3145-1755
Keywords: security of data; Markov processes; Monte Carlo methods; power system reliability; heat pumps; cyber-physical systems; power engineering computing; power system reliability assessment; heat pump system; smart power system; communication technologies; cyber-physical interactive threats; system infrastructure; cyber-intrusion process; impact assessment framework; cyber-detection; system recovery process; cyber-physical interactive operation models; Markov-chain based framework; cyber-intrusion detection-time distributions